KEMANDIRIAN PADA REMAJA AWAL ANTARA ORANG TUA DOUBEL PARENT DAN ORANG TUA TUNGGAL (SINGLE PARENT) : KEMANDIRIAN PADA REMAJA AWAL ANTARA ORANG TUA DOUBEL PARENT DAN ORANG TUA TUNGGAL (SINGLE PARENT) - hasanah, uswatun (IDEA: Jurnal Psikologi, 2023)
Independence refers to the belief in one's own ability to solve problems without the help of others, without being controlled by others This study aims to determine the differences in independence in early adolescents between double parents and tuggal parents (single parents) in Jombang,. With a sample size of 40 early adolescents aged 13-17 years, data collection was obtained from the results of a list of questions in the form of a questionnaire or self-reliance questionnaire given to early adolescent research subjects with double parents and single parents (single parent) in Jombang. This type of research is quantitative research using the deferential method with the aim of finding differences in 2 variables using t-test statistical analysis. The results of statistical tests and obtained the value of t = 5.921; p = 0.001 . Independence of adolescents with single parent (A1) has a mean value of M1 = 47.436 and independence of adolescents with double parent (A2) has a mean value ofM2 = 41.554 The difference in the mean score of independence between adolescents with single parent and adolescents with double parent is p = 0.001.